Climate and Environmental Risk Management in the Banking Sector : A Focus on Agriculture in Czechia - Sosnytska, Alina (2024)
Sustainable development depends on healthy ecosystems; however, climate change and environmental degradation pose significant risks to businesses and financial systems. The agricultural sector is particularly vulnerable to climate and environmental (C&E) risks due to its substantial climate and nature-related impacts and dependencies. Consequently, financial institutions may face heightened credit risk driven by C&E transition and physical risks associated with agricultural lending. Yet, the banking sector lacks detailed guidance for assessing natural capital credit risk in agriculture, a challenge further complicated by the significant variation in material risks across agricultural sectors and regions. This thesis investigates climate and environmental risks that are likely to be material in credit risk assessments within the agricultural sector in Czechia. It identifies primary climate and nature-related impact and dependency risk drivers that may lead to transition or physical risks and opportunities. Ultimately, the thesis proposes strategies for mitigating C&E risks through effective risk management practices, sustainable investments, and procedural improvements. Key implementation challenges include the complexity and interconnectivity of natural capital processes, technological barriers and costs, and the need for a coordinated climate-nature transition within agriculture and the banking sector.